Academic Achievement Development on al-Qur’an Subject; Entitled Beginning of Reading al-Qur’an with Qiroat Through Computer Assisted Instruction (CAI) for Islamic Studies Stage Students, Year 2 - Jeksoh, Alawi; Sulong, Abdulramae; Haengyama, Muhammadsuhaimi (MENARA : Journal of Islamic and Contemporary Issues, 2025)
The objectives of this research were 1) to develop and find the effectiveness of computer-assisted instruction on the beginning of reading al-Qur’an with qiroat for islamic studies stage students, Year 2 according to the 80/80 standard; 2) to study learning achievements by using computer-assisted instruction. 3) to study the students’ satisfaction by computer-assisted instruction on the beginning of reading al-Qur’an with qiroat. The target population were 25 students which conducted with students in the first semester of the academic year 2024, The research tools consisted of 1) 8 Lessions of computer-assisted instructions on the beginning of reading al-Qur’an with qiroat 2) an achievement test, which was multiple choice, with 4 choices, 40 items. 3) the satisfaction auestioning form of students who studied with the learning activity plans on the beginning of reading al-Qur’an with qiroat. The statistics used were mean, standard deviation, and t-Test value. The results showed that; 1. The efficiency of the CAI lessons on the beginning of reading al-Qur’an with qiroat was equal to E1/E2 83.50/88.20. 2. The academic achievement of students who studied with computer-assisted instruction on the beginning of reading al-Qur’an with qiroat had a significantly higher average score than before learning, at a significance level of 0.05. 3. The students’ satisfaction with computer-assisted instruction on the beginning of reading al-Qur’an with qiroat had an average score of 4.58 indicating a very high level of satisfaction.